RADICALISM AND THE SOLUTIVE EFFORTS OF ISLAMIC EDUCATION - Hisnuddin, Hisnuddin; Suwahyu, Irwansyah (Universitas Islam Negeri Alauddin Makassar, 2018)
This article examines the radicalism that occurs in the world of education and how Islamic education provides solutions to overcome them. This study was conducted to explain the importance of Islamic education in life to counter radicalism, especially in countries with diversity such as Indonesia. This research is a library research in which data is obtained through documents analyzed by content analysis. The results of this study suggest that Islamic education is an appropriate vehicle for building multiculturalism awareness and as one of the important media that can shape the way one's life style or community. This is proven by the Islamic concepts of as-sawiyah (equality), al-'is or justice, al-hurriyah or freedom as well as tasamuh or tolerance which is the basic capital of multiculturalism theology.